2008
DOI: 10.1038/modpathol.2008.88
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological features and global genomic copy number alterations of pilomyxoid astrocytoma in the hypothalamus/optic pathway: comparative analysis with pilocytic astrocytoma using array-based comparative genomic hybridization

Abstract: Pilomyxoid astrocytoma is a recently identified variant of pilocytic astrocytoma. We studied 11 circumscribed astrocytomas with focal (n ¼ 5) or diffuse (n ¼ 6) pilomyxoid features and compared them with 17 pilocytic astrocytomas from the hypothalamic/chiasmatic region in children. In one patient, a tumor that recurred after initial surgery had changed from pure-form pilomyxoid astrocytoma to the mixed form. The presence of a pilomyxoid area was associated with shorter survival. Next, we compared the comprehen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 40 publications
4
16
0
Order By: Relevance
“…Amplification of 8q24.3 occurs commonly in sporadic breast cancer (45) and squamous cell cervical carcinoma (46), two types of carcinomas that display a tendency toward SIPL1 expression with PTEN positivity. Increases in the copy number at the 8q24.3 locus were also observed in astrocytoma (47), gastroesophageal junction cancer (48), prostate cancer (49), chemoresistant ovarian cancer (50), larynx and pharynx squamous cell carcinoma (51), liver cancer (52,53), and colorectal cancer (54,55). Taken together, these observations suggest that amplification of SIPL1 facilitates the tumorigenesis of multiple human cancers.…”
Section: Discussionmentioning
confidence: 98%
“…Amplification of 8q24.3 occurs commonly in sporadic breast cancer (45) and squamous cell cervical carcinoma (46), two types of carcinomas that display a tendency toward SIPL1 expression with PTEN positivity. Increases in the copy number at the 8q24.3 locus were also observed in astrocytoma (47), gastroesophageal junction cancer (48), prostate cancer (49), chemoresistant ovarian cancer (50), larynx and pharynx squamous cell carcinoma (51), liver cancer (52,53), and colorectal cancer (54,55). Taken together, these observations suggest that amplification of SIPL1 facilitates the tumorigenesis of multiple human cancers.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, results of a recent genome-wide gene copy number analysis provided additional argument for the "spectrum disease" thesis (Jeon et al, 2008). Interestingly, the same study reported worse survival of patients with the above mentioned mixed-form PMA/PA in comparison to classical chiasmatic-hypothalamic PAs and also observed one PMA that transferred into a PA after recurrence.…”
Section: Discussionmentioning
confidence: 79%
“…Most studies underline the histological resemblance of PMA to PA and propose a similar astrocytic origin, however, the cell origin and exact pathogenesis of the PMA are still unclear (Fuller et al, 2001;Chikai et al, 2004;Jeon et al, 2008). Growing evidence suggests that the two tumor types are pathologically and genetically related.…”
Section: Discussionmentioning
confidence: 99%
“…Pilocytic astrocytoma and pilomyxoid astrocytoma have signifi cant overlap in clinical and radiographic features, histologic features [ 126 ], and genetic aberrations [ 127 ]. Tumors with intermediate features are typically found in older patients, and cases of "maturation" of pilomyxoid astrocytoma into pilocytic astrocytoma [ 126 ] have been documented.…”
Section: Pilocytic-pilomyxoid Spectrummentioning
confidence: 99%